Impact of adjuvant imatinib on bone and muscle density in patients with resected gastrointestinal stromal tumors - Claudia Angela Maria Fulgenzi; Andrea Napolitano; Eliodoro Faiella; Laura Messina; Gennaro Castiello; Flavia Paternostro; Marianna Silletta; Francesco Pantano; Giuseppe Tonini; Daniele Santini; Bruno Vincenzi (Journal of Bone Oncology, 2022)
Adjuvant treatment with Imatinib is the standard of care for high-risk resected GISTs. Imatinib is known to have an impact on bone mineral density in patients affected by chronic myeloid leukemia, however this effect has never been investigated in GISTs.We retrospectively evaluated, on CT scans, the effect of adjuvant Imatinib (400 mg/die) on bone mineral density and muscle composition in 14 patients with surgically resected GISTs and in a control group of 8 patients who did not received any treatment. The effect of bone and muscle composition on Imatinib-tolerance was assessed as well.Overall patients receiving Imatinib experienced an increase in bone mineral density during treatment (p = 0.021); with higher increase in patients with basal values < 120 mg/cm3 (p = 0.002). No changes were observed in the control group (p = 0.918).Skeletal muscle index and lean body mass did not change over time during Imatinib therapy; however, patients with lower lean body mass and lower body mass index experienced more grade 3 treatment related toxicities (p = 0.024 and p = 0.014 respectively). We also found a non-significant trend between basal BMD and grade 3 toxicities (p = 0.060)